Synthetic inhibition of SREBP2 and the mevalonate pathway blocks rhabdomyosarcoma tumor growth in vitro and in vivo and promotes chemosensitization - Silvia Codenotti; Michela Asperti; Maura Poli; Luisa Lorenzi; Alberto Pietrantoni; Matteo Cassandri; Francesco Marampon; Alessandro Fanzani (Molecular Metabolism)
Objective: The aim of the present study was to investigate the effects of targeting the mevalonate pathway (MVP) in rhabdomyosarcoma (RMS), a soft tissue tumor with a prevalence in young people. Methods: In silico analyses of RNA datasets were performed to correlate MVP with RMS patient survival. The sensitivity of RMS cell lines to MVP inhibitors was assessed in vitro by analysis of cell growth (crystal violet and clonogenic assays), cell migration (wound healing assay), cell survival (neutral red assay), and oxidative stress (ROS assay). The effects of MVP inhibitors were tested in vivo by analyzing RMS xenografts grown in NOD/SCID mice. Quantification of protein targets was performed using immunoblotting or immunohistochemistry analyses. Results: In silico analysis showed upregulation of sterol regulatory element-binding protein 2 (SREBP2) and MVP genes, including 3-Hydroxy-3-Methylglutaryl-CoA Reductase (HMGCR), farnesyl-diphosphate synthase (FDPS), squalene epoxidase (SQLE), which correlated with worse overall patient survival. Targeting of MVP in human RD and RH30 lines by inhibitors of SREBP2 (fatostatin), HMGCR (lovastatin and simvastatin), and FDPS (zoledronic acid) resulted in impaired cell growth, migration, and viability, and increased oxidative cell death in combination with actinomycin D. Conversely, cholesterol (CHO) supplementation enhanced cell growth and migration. Fatostatin and lovastatin produced rapid attenuation of Erk1/2 and Akt1 signaling in RMS lines, and oral administration of lovastatin reduced tumor mass growth of xenografted RD cells in NOD/SCID mice. Finally, we found that forced Akt1 activation in RD cells was sufficient to drive SREBP2, HMGCR and SQLE protein expression, promoting increased susceptibility to MVP inhibitors. Conclusions: These data suggest that the Akt1, SREBP2 and MVP axis is critical for RMS tumor growth, migration, and oxidative stress protection primarily through maintaining adequate CHO levels that enable proper intracellular signaling. Therefore, stimulating CHO depletion via SREBP2 and MVP inhibition may represent a viable option to improve the combination therapy protocol, especially in pAkt1-positive RMS.